Pakistan at 100 : Governance and Institutions - Muhula, Raymond (World Bank, Washington, DC, 2019)
This policy note was prepared in parallel to the report Pakistan at 100- Shaping the Future. The report Pakistan at 100 discusses options to accelerate and sustain growth in Pakistan so that the country becomes an upper middle-income country when it turns hundred years old in 2047. This policy note discusses the need for strong governance to accelerate and sustain Pakistan’s growth. Strong governance will require improved transparency and accountability, so policies are designed and implemented to benefit Pakistan’s population.